HR managers' talent philosophies: prevalence and relationships with perceived talent management practices. Issue 4 (21st February 2020) - Meyers, Maria Christina; van Woerkom, Marianne; Paauwe, Jaap; Dries, Nicky
Abstract: HR managers have different beliefs about the nature, value, and instrumentality of talent—referred to as 'talent philosophies'. In line with cognitive psychology, we reason that talent philosophies are similar to mental models that influence how HR managers interpret and use talent management (TM) practices within their organizations. In this article, we explore the prevalence of four different talent philosophies (exclusive/stable; exclusive/developable; inclusive/stable; inclusive/developable) in a sample of 321 HR managers. We then explore how talent philosophies relate to organizational context (i.e. size, ownership form, multinational orientation) as well as to HR managers' perceptions of their organization's TM practices. Cluster analysis corroborated the presence of the four talent philosophies in our dataset. All four talent philosophies were represented almost equally often in the overall dataset. Organizational size was found to be related to talent philosophies, such that HR managers who worked in smaller organizations were more likely to hold an inclusive talent philosophy. We also found support for the relationship between talent philosophies and perceptions of the exclusiveness or inclusiveness of the organization's definition of talent, and its degree of workforce differentiation. Contrary to expectations, results did not support a link between talent philosophies and perceived talent identification criteria.